Role of Farmers’ Cooperatives in Income Generation: A Study of Chitwan District - Dhakal, Chandra Prasad (International Research Journal of MMC, 2024)
The farmer cooperatives are the kinds of cooperative that only farmers are involved to run the cooperative and the purpose of the cooperatives is to work for the wellbeing for farmers. The study focuses on role of farmers’ cooperative in income generation. Main objectives of the study analyzed the situation of farmers’ cooperatives of Chitwan and their activities related to income generation of the members. The study followed descriptive method and data were analyzed both qualitative and quantitative research design. Conclusion of this study was based on primary data. In Chitwan only 15% cooperatives were related to farmers’ cooperatives and these cooperatives have no enough capital and investment, however, the attempt of cooperative in income generating was excellence. Income generating activities of the cooperatives created new hope among the members. Profit of the cooperatives showed that those cooperatives were in a right track and in future the cooperatives can be played more effective role in income generation.